Translation with Cross-cultural Adaptation of Cerebral Palsy Quality of Life Questionnaire for Children into Nepali and its Psychometric Properties - Shrestha, N.; Suwal, A.; KC, S.; Adhikari, S. P. (Kathmandu University Medical Journal, 2020)
Background Cerebral Palsy Quality of Life questionnaire for children primary caregiver version is the widely used condition specific outcome measure which assesses the wellbeing of the child. It has been translated to many languages and shows excellent psychometric properties. Availability in Nepali would facilitate the use in clinical practice and research in Nepali population. Objective The objective of this study was translation with cross-culturally adaption of Cerebral Palsy Quality of Life questionnaire for children primary caregiver version into Nepali and assess its psychometric properties. Method Cross-cultural adaptation was performed using forward and backward translation protocol. Pretesting was done on six participants to confirm that the original concept was preserved. The Nepali version of questionnaire was administered twice for data collection. The feasibility, sensitivity, internal consistency and test-retest reliability was determined. Result Culturally adapted Nepali version showed good feasibility only the domain “Access to service” had a highest missing score related to use of the special equipment, attending kindergarten and applying for respite care. Floor and ceiling effect were < 15% in all the domains except in few items of “Pain and impact of disability” and “Social well being and acceptance”. Test retest reliability (0.82 – 0.91) and internal consistency (0.68 – 0.84) was good. There were weak association of domains with the gross motor functional classification system level. Conclusion Cross-culturally adapted Nepali Cerebral Palsy Quality of Life questionnaire for children primary caregiver was developed. It demonstrates good psychometric properties confirming to assess quality of life of children with Cerebral palsy in Nepal.